A Brief Neuropsychological Battery for Measuring Cognitive Functions Associated with Obesity - Hovens, Iris B. (Obesity (Silver Spring), 2019)
OBJECTIVE: Although ample evidence links obesity to cognitive dysfunction, the trajectory of cognitive change, the underlying mechanisms, and the involvement of related factors, such as metabolic disease and diet remain unclear. To support further investigations of body mass index (BMI) and cognition, we aimed to create a concise test battery to be used in future trials. METHODS: We regressed 20 neurocognitive measures on BMI in the Human Connectome Project Healthy Young Adult S1200 data release using Linear Mixed Models and adjusting for major confounders. We then identified measures using LASSO regression analysis to select tests most strongly associated with BMI. To guide further test selection we visualized the explained variance for each variable in the final model. RESULTS: BMI was negatively associated with 7 neurocognitive measures. Variable selection yielded a model including years of education and -in order of model weight- Delay Discounting, the Relational Task, Penn Progressive Matrices, Oral Reading Recognition, the Variable Short Penn Line Orientation and Penn Word Memory. CONCLUSION: This resulted in a ~ 40--minutes test battery for the BMI-cognition relationship in young adults that can be used in trials investigating the interrelationship between obesity and cognitive performance.